Об универсальности двузначной логики - Дышкант, Татьяна Николаевна (Харківський національний університет ім. В. Н. Каразіна, 2010)
В связи с углублением и расширением познания, выражаемым выходом на изучение объектов, принципиально отличающихся от объектов макромира, с одной стороны, и, попыткой дать обоснования основным математическим положениям, с другой стороны, встает вопрос о методах и основаниях познания, в том числе, и о логике. О недоверии к универсальности двузначной логики свидетельствует возникновение большого числа самых разнообразных логик. В данной статье рассматривается насколько обосновано данное недоверие.

In connection with deepening and expansion of cognition, by the expressed output on the study of objects on principle different from the objects of macrocosm, from one side, and, from other side, a question gets up an attempt to give the grounds to the substantive mathematical provisions about methods and grounds of cognition, including, and about logic. About the mistrust the origin of large number of most various logics testifies to universality of binary logic. In this article is examined as far as this mistrust is grounded.
About universality of binary logic
Keywords: многозначная логика; закон исключенного третьего; интуитивизм; физика микромира; binary logic; multiple-valued logic; law of the eliminated third; intuitionalism; physics of microcosm